2017
DOI: 10.5539/gjhs.v10n1p48
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction among University Students and Its Relationship with Academic Performance

Abstract: Background and Objective: Smartphone use is almost universally relied on among college students. Whether smartphone addiction among college students has a negative predictive effect on academic performance is hardly studied. Previous research found an apparent association between smartphone use and academic achievement partly explained by the nature of the task the student is engaged in when using a smartphone. This study aims to assess the relationship between smartphone addiction and students' academic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Studies have shown the use of smartphone for learning purpose as a protective factor over unproductive use for smartphone addiction [30,31]. In our study only 12/250 (M = 5 and F = 7) participants used smartphone solely for study purpose.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have shown the use of smartphone for learning purpose as a protective factor over unproductive use for smartphone addiction [30,31]. In our study only 12/250 (M = 5 and F = 7) participants used smartphone solely for study purpose.…”
Section: Discussionmentioning
confidence: 70%
“…For the sake of simplicity, we have adopted the term “excessive smartphone use” in this manuscript to refer to the complete range of problem smartphone use patterns. Excessive smartphone use is associated with a range of negative social and health outcomes, such as poor academic and work performance [7, 8], reduced in-person social interaction [9, 10], traffic road accidents [11], and mental health problems (depression and anxiety) [5, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the use of smartphone for learning purpose as a protective factor over unproductive use for smartphone addiction. [30,31] In our study only 12/250 (M=5 and F=7) participants used smartphone solely for study purpose. This could as well be a reason for higher percentage of smartphone addiction in the current study.…”
Section: Discussionmentioning
confidence: 99%